Intra-amniotic inflammation and birth weight in pregnancies with preterm labor with intact membranes: A retrospective cohort study - Matulova, Jana; Kacerovsky, Marian; Bolehovska, Radka; Kukla, Rudolf; Bostik, Pavel; Kolarova, Klara; Frydrychová, Simona; Jacobsson, Bo; Musilova, Ivana (Frontiers in Pediatrics, 2022)
Objective: To assess the association between newborn birth weight and the presence of intra-amniotic infection, presence of sterile intra-amniotic inflammation, and absence of intra-amniotic inflammation in pregnancies with preterm labor with intact membranes. Methods: A total of 69 pregnancies with preterm labor with intact membranes between gestational ages 22+0 and 34+6 weeks who delivered within seven days of admission were included in this retrospective cohort study. Transabdominal amniocentesis to determine the presence of microorganisms and/or their nucleic acids in amniotic fluid (through culturing and molecular biology methods) and intra-amniotic inflammation (according to amniotic fluid interleukin-6 concentrations) were performed as part of standard clinical management. The participants were further divided into three subgroups: intra-amniotic infection (presence of microorganisms and/or nucleic acids along with intra-amniotic inflammation), sterile intra-amniotic inflammation (intra-amniotic inflammation alone), and without intra-amniotic inflammation. Birth weights of newborns were expressed as percentiles derived from the INTERGROWTH-21st standards for i) estimated fetal weight and ii) newborn birth weight. Results: No difference in birth weights, expressed as percentiles derived from the standard for estimated fetal weight, was found among the women with intra-amniotic infection, with sterile intra-amniotic inflammation, and without intra-amniotic inflammation (with infection, median 29; with sterile inflammation, median 54; without inflammation, median 53; p = 0.06). Differences among the subgroups were identified in the birth weight rates, expressed as percentiles derived from the standard for estimated fetal weight, which were less than the 10th percentile (with infection: 20%, with inflammation: 13%, without inflammation: 0%; p = 0.04) and 25th percentile (with infection: 47%, with inflammation: 31%, without inflammation: 9%; p = 0.01). No differences among the subgroups were observed when percentiles of birth weight were derived from the birth weight standard. Conclusions: The presence of intra-amniotic inflammatory complications in pregnancies with preterm labor with intact membranes prior to the gestational age of 35 weeks was associated with a higher rate of newborns with birth weight less than the 10th and 25th percentile, when percentiles of birth weight were derived from the standard for estimated fetal weight.